Khilafiyah About The Eternity of Hellfire (A Study of The Interpretation of The Meaning Ahqaba in Tafsir At-Thabari By Ath-Thabari) - Wahyudi Wahyudi; Firmansyah Sistiawan; Wildan Taufiq; Wildan Hasan Abdullah; Raihani Salma Amatullah (Journal Analytica Islamica, 2023)
This article will discuss the meaning of ahqaba in the Al-Quran. The word ahqaba in the Qur'an is found in two verses and two derivations. In QS Al-Kahf verse 60 and QS An-Naba verse 23. The meaning of ahqaba in QS Al-Kahf verse 60 means Zamanan or dahran (for a century). As for QS An-Naba verse 23, there are many opinions regarding the meaning of ahqaba, some say it lasts 300 years, 80 years, 7000 years and every day is the same as 1000 years. There are also those who interpret ahqaba as long as Allah SWT wills. And finally, there are those who say that the verse Labitisina fiha ahqaba, this verse has been combined with the verse falan nazidakum illa 'adzaba. The method used in this article is a type of qualitative research where researchers try to understand and interpret human behavioral interaction events in certain situations from their own point of view. For this research, data was collected through literature study with a content analysis approach.Artikel ini akan membahas tentang makna ahqaba dalam Al-Qura'an. Kata ahqaba dalam Al-Qur'an di temukan ada dua ayat dan dua derivasi. Pada QS Al-Kahfi ayat 60 dan QS An-Naba ayat 23. Makna ahqaba pada QS Al-Kahfi ayat 60 bermakna zamanan atau dahran (selama satu abad). Adapun pada QS An-Naba ayat 23, makna ahqaba banyak pendapat dalam memaknainya, ada yang berpendampat selama 300 tahun, 80 tahun, 7000 tahun dan setiap harinya sama dengan 1000 tahun. Ada juga yang menafsirkan ahqaba dengan selama Allah swt menghendaki. Dan terakhir ada yang mengatakan bahwa ayat Labitisina fiha ahqaba, ayat ini sudah di mansukh dengan ayat falan nazidakum illa ‘adzaba. Metode yang di gunakan dalam arikel ini adalah jenis penelitian kualitatif di mana peneliti mencoba memahami dan menafsirkan peristiwa interaksi tingkah laku manusia dalam situasi tertentu dari sudut pandang mereka sendiri. Untuk penelitian ini, data dikumpulkan melalui studi pustaka dengan pendekatan analisis isi.